Od lęku przed śmiercią do terapii śmiechem – refleksje nad „dobrą” starością w kulturze późnej nowoczesności - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article describes so called two strategies of life, modern and post-modern by Zygmunt Bauman. It’s can be described as two cultural ways of managing of existential fear of death. This problem is particularly involved in the last period of life, old age. The old age is the time of losing of vital energy, time of loneliness and identity challenges. What’s properly called „good” old age? What does it promote and what does it limits? Can we talk about it in terms of youth, such as success, satisfaction, self-realization? This phenomenon will be shown in the context of psychological and theological reflection on the wisdom, narcissism, „good” aging and death. An illustration of consideration will be the life of the main character of the film Gloria directed by Sebástian Lelio.
Keywords: autotranscendencja; ciało; dobra starość; lęk przed śmiercią; mądrość; narcyzm; starość; starzenie się; strategie życia